Effective parameters on the behavior of CFDST columns - Farajpourbonab, Ebrahim (Journal of Applied Engineering Science, 2017)
Concrete Filled Double Skin Steel Tubular (CFDST) columns could be considered as a new type of concrete filled steel tubular (CFT) columns. These columns are composed of two steel tubes in the concentric configurations with concrete between them. In the current study, finite element method was used to analyze the effects of load application, type of material, and geometric parameters of the specimens. It was found that the results obtained from finite element analysis show good agreement with available experimental results. Findings of the current study clearly indicate the high ductility and strength of CFDST columns under axial loading.  The results show the significant impact of yield stress of steel section, compressive strength of concrete, thickness and diameter variations on the strength and ductility of CFDST columns.